Parasitism of two strains of Heterorhabditis bacteriophora on the subterranean burrowing bug Cyrtomenus bergi (Hemiptera: Cydnidae) - BARBERENA, MARÍA FERNANDO; BELLOTTI, ANTHONY C. (Revista Colombiana de Entomología, 1998)
The subterranean burrowing bug, Cyrtomenus bergi is a pest that damages cassava roots. Its feeding mode facilitates the introduction of root pathogens, deteriorating root quality. The present research, undertaken at the International Center for Tropical Agriculture (ICTA), initiated the development of the methodology to mass rear the nematode Heterorhabditis bacteriophora, measured the parasitic capacity of two strains LFR92 and SQC92 on C. bergi, determined the most susceptible development stage; distinguished parasitic comparison between strains, determined if C. bergi responds differentially to several doses of n/ml, and the DL50 for each strain. There were no significant differences in the parasitic capacity between the strains LFR92 and SQC92 of H. bacteriophora. The most susceptible stage of C. bergi to H. bacteriophora parasitism was the fifth nymphal stage for both strains. C. bergi showed a differential response to several doses of n/ml. The DL50 for SQC92 was determined as 826 n/ml with limits [545:1137], and for LFR92 as 720 n/ml, with limits [81:1551]. The strain LFR92 proved to be the more aggressive of the two strains. H. bacteriophora is a potential control agent for C. bergi since it has presented high levels of parasitism and because it’s a native strain.